2005
DOI: 10.1261/rna.7198205
|View full text |Cite
|
Sign up to set email alerts
|

Seawi—a sea urchin piwi/argonaute family member is a component of MT-RNP complexes

Abstract: The piwi/argonaute family of proteins is involved in key developmental processes such as stem cell maintenance and axis specification through molecular mechanisms that may involve RNA silencing. Here we report on the cloning and characterization of the sea urchin piwi/argonaute family member seawi. Seawi is a major component of microtubule-ribonucleoprotein (MT-RNP) complexes isolated from two different species of sea urchin, Strongylocentrotus purpuratus and Paracentrotus lividus. Seawi co-isolates with purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Interestingly, dDcp 1 of the oskar mRNP complex in Drosophila oocytes mislocates in mutants in which microtubule organization is abnormal (Lin et al 2006). Also, the Argonaute 1 homolog from sea urchins, Seawi, has been identified in a microtubule-associated protein complex that localizes in cytoplasmic puncta (Rodriguez et al 2005). It is not known whether SGs contain proteins associated with microtubules, but we and others (Ivanov et al 2003) observed that microtubule integrity is necessary for SG assembly.…”
Section: Hdac6 Links the Microtubule System And Sgsmentioning
confidence: 82%
“…Interestingly, dDcp 1 of the oskar mRNP complex in Drosophila oocytes mislocates in mutants in which microtubule organization is abnormal (Lin et al 2006). Also, the Argonaute 1 homolog from sea urchins, Seawi, has been identified in a microtubule-associated protein complex that localizes in cytoplasmic puncta (Rodriguez et al 2005). It is not known whether SGs contain proteins associated with microtubules, but we and others (Ivanov et al 2003) observed that microtubule integrity is necessary for SG assembly.…”
Section: Hdac6 Links the Microtubule System And Sgsmentioning
confidence: 82%
“…Taken together the results suggest that piRNAs have a dynamic expression pattern in the early sea urchin embryo. This increase of piRNA expression may correspond with the specification of the piwi -positive small micromere lineage (Juliano et al, 2006; Rodriguez et al, 2005). …”
Section: Resultsmentioning
confidence: 98%
“…Recent studies have suggested that PIWI proteins in sea urchin (Seawi) and Xenopus (Xiwi) can interact with the MTs of the meiotic spindle (Rodriguez et al 2005;Lau et al 2009), while fly ovarioles with mutations in any of several piRNA pathway genes, including spn-E, aub, and armi, have disorganized MTs (Chen et al 2007;Klattenhoff et al 2007;Pane et al 2007). This raises the possibility for either a functional role of PIWI proteins in the machinery that impacts on MT organization (in addition to transposon silencing), a role of the MT cytoskeleton in piRNA generation, or both.…”
Section: Discussionmentioning
confidence: 99%